Dominance of short form videos: Cross-age analysis of TikTok’s influence - Aliyah Balogun-Ibijunle; Omotola Ogunbola; Ololade Olatunji; Aduloju Doyinsola; Omolara Akin-Odukoya; Sylvester Ojenagbon; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
Social media platforms have evolved rapidly, transitioning to facilitate new modes of content consumption. Short-form videos have emerged as a dominant format, epitomized by TikTok's widespread success. This study aims to conduct a comprehensive cross-age examination of TikTok's influence through the dominance of short videos. Qualitative methods including semi-structured interviews were employed to collect primary data from participants of varying ages. Specific objectives involve investigating usage patterns, perceived influences on behaviour and attitudes, potential benefits and drawbacks. The findings indicate diverse yet creative engagement across age groups. Younger users’ demonstrated constant usage yet faced content restrictions, while older participants leveraged TikTok professionally. Educational and skills-based advantages coexisted with algorithmic unpredictability challenges. TikTok addressed brief attention spans yet privacy concerns require addressing. Thematic analysis revealed patterns like nighttime relaxation usage. Educational and motivational content stimulated learning. Professional development through modeling, photography showcasing emerged. Creativity, expression and skills growth represented positive influences versus unpredictable visibility frustrations. TikTok reshaped consumption habits yet privacy integration oversight remained. This study contributes a contextualized understanding of TikTok's multi-faceted impacts. It presents a balanced perspective appreciating opportunities and challenges to harness social technologies productively.